Research on Data Mining Application of Orthopedic Rehabilitation Information for Smart Medical - Mao Ye; Hangzhou Zhang; Li Li (IEEE Access, 2019)
Due to the small scale, low technical level, and limited scope of application of artificial intelligence in the field of traditional Chinese medicine orthopedics, there are many problems in the development of this area. Driven by precise and minimally invasive medical concepts, the integration of artificial intelligence and data mining technologies (such as the Internet, cloud computing, and big data) will further profoundly change the face of smart healthcare in the future, which will bring great challenges to traditional Chinese medicine orthopedics, and Change opportunities for your own development. In order for artificial intelligence to provide good diagnosis and treatment services for a large number of patients with orthopaedic diseases, progress still needs to be made with the technology and joint efforts of many orthopaedic experts and scholars. This article uses data mining techniques to optimize orthopedic rehabilitation information. Test results show that the system is faster and more convenient. Artificial intelligence technology will be used for intelligent medical treatment of orthopedic diseases in the future. It will become an essential assistant for clinicians and make a significant contribution to the diagnosis of various orthopedic diseases.